2019
DOI: 10.1016/j.jsams.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

1.5 mile run time and body mass predict 8 mile loaded march performance, irrespective of sex

Abstract: 1.5mile run time and body mass predict 8mile LM performance with no further improvement gained in the model by including sex as a variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Female soldiers with ACFT-scaled scores equal to males may have weaker raw scores than those males, which could indicate some limitations in tasks requiring the qualities measured in those tests (e.g., female soldiers may have equivalent sex-scaled deadlift scores with male soldiers, but a lower deadlift load, which indicates lesser strength). These findings also support previous research that has indicated female military personnel may require specific fitness training to reduce performance gaps and injury risk compared to their male counterparts [ 9 , 33 , 42 , 43 ] and the trend of males generally scoring higher than females in military fitness testing [ 32 , 33 , 34 , 35 ]. Data from the US Army also shows a gap in performance between the sexes [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Female soldiers with ACFT-scaled scores equal to males may have weaker raw scores than those males, which could indicate some limitations in tasks requiring the qualities measured in those tests (e.g., female soldiers may have equivalent sex-scaled deadlift scores with male soldiers, but a lower deadlift load, which indicates lesser strength). These findings also support previous research that has indicated female military personnel may require specific fitness training to reduce performance gaps and injury risk compared to their male counterparts [ 9 , 33 , 42 , 43 ] and the trend of males generally scoring higher than females in military fitness testing [ 32 , 33 , 34 , 35 ]. Data from the US Army also shows a gap in performance between the sexes [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…This was because the arduous tasks of combat will not change for a soldier because of their sex or age. As previously noted, and given the data from this study and previous research [ 19 , 32 , 33 , 34 , 35 ], switching to a scoring system based on sex and age may serve to hide deficiencies in fitness that can hinder job performance. Inadequate fitness can put soldiers at greater risk, as combat tactics are reliant on the assumption of every soldier on a team being able to perform the tasks required of their job.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A combination of resistance and aerobic training has been associated with improvements in load carriage performance [106][107][108]. Studies show that upper body relative strength (strength per unit of body mass) is more highly correlated to loaded road march performance than lower body relative strength [108,113]. Furthermore, increases in aerobic and musculoskeletal fitness are likely essential to prevent future injury, with lower levels of these measures associated with an increased risk of injury in soldiers [114][115][116].…”
Section: Physical Conditioning and Rehabilitation For Soldier Load Carriage Tasksmentioning
confidence: 99%